2011
DOI: 10.2174/187152811796117753
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Gelatinase-Associated Lipocalin (NGAL) as a New Biomarker for Non – Acute Kidney Injury (AKI) Diseases

Abstract: Neutrophil gelatinase-associated lipocalin, or NGAL, an acute phase protein, is part of the lipocalin family. NGAL is highly induced in inflammatory conditions and ischemia, and is a critical component of innate immunity to bacterial infection. Recently, NGAL has been proven as an emerging biomarker for predicting acute kidney injury (AKI). Meanwhile, numerous studies have also demonstrated that NGAL may be a potential biomarker for the diagnosis, prediction, prevention, and prognosis of non--AKI diseases such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 76 publications
1
24
0
1
Order By: Relevance
“…It is considered an acute-phase reactant protein, highly induced in inflammatory conditions [16] and endothelial damage [17,27]. In nonpregnant individuals, elevated serum levels of NGAL have been related with hypertension [28], acute kidney injury (for its prediction and prognosis) [29], and with the severity of renal impairment in chronic kidney disease [30]. It is then plausible that NGAL levels are increased in women with preeclampsia that is characterized by placental hypoxia and ischemia leading to systemic excessive oxidative stress in association with inflammation and endothelial dysfunction [31].…”
Section: Discussionmentioning
confidence: 99%
“…It is considered an acute-phase reactant protein, highly induced in inflammatory conditions [16] and endothelial damage [17,27]. In nonpregnant individuals, elevated serum levels of NGAL have been related with hypertension [28], acute kidney injury (for its prediction and prognosis) [29], and with the severity of renal impairment in chronic kidney disease [30]. It is then plausible that NGAL levels are increased in women with preeclampsia that is characterized by placental hypoxia and ischemia leading to systemic excessive oxidative stress in association with inflammation and endothelial dysfunction [31].…”
Section: Discussionmentioning
confidence: 99%
“…Its expression is highly upregulated in damaged epithelial cells, during infl ammation, neoplastic conditions, cardiovascular diseases, infections and renal disorders. 50 NGAL can be detected in urine within two hours of kidney damage, hence it is considered as the best and the earliest markers of acute kidney damage. 50,51 In some recent studies serum level of NGAL was found to be increased at the end of second trimester in women who subsequently developed PE compared to control group.…”
Section: Neutrophil Gelatinase-associated Lipocalin (Ngal)mentioning
confidence: 99%
“…50 NGAL can be detected in urine within two hours of kidney damage, hence it is considered as the best and the earliest markers of acute kidney damage. 50,51 In some recent studies serum level of NGAL was found to be increased at the end of second trimester in women who subsequently developed PE compared to control group. 47,49,52 A positive correlation of serum NGAL was found with the systolic and diastolic blood pressure and with proteinuria.…”
Section: Neutrophil Gelatinase-associated Lipocalin (Ngal)mentioning
confidence: 99%
“…Elevation of NGAL occurs in many other conditions, including chronic kidney disease, vascular disorders, cancer, preeclampsia, and allergy. 16 Thus, although urinary NGAL may represent an early sensitive noninvasive urinary biomarker for populations with ischemic and nephrotoxic AKI, it is not useful for management decisions in an individual patient. 17 A number of other potential biomarkers have been studied, including interleukin-18 (IL-18), kidney injury molecule-1 (KIM-1), and liver-type fatty acid-binding protein (L-FABP) ( Table 2).…”
Section: Ormentioning
confidence: 99%
“…L'élévation de la NGAL survient dans de nombreuses autres circonstances, y compris la maladie rénale chronique, les troubles vasculaires, la prééclampsie et l'allergie. 16 Ainsi, même si la NGAL urinaire peut représenter un biomarqueur urinaire précoce, sensible et non invasif, chez les populations ayant une LRA ischémique et néphrotoxique, elle n'est pas utilisable pour les décisions de prise en charge d'un patient particulier. 17 Plusieurs autres biomarqueurs potentiels ont été étudiés, y compris l'interleukine-18 (IL-18), la kidney injury molecule-1 (KIM-1, molécule de lésion rénale) et la protéine de liaison des acides gras de type hépatique (L-FABP, liver-type fatty acid-binding protein) (Tableau 2).…”
Section: Orunclassified